2018
DOI: 10.1016/j.rboe.2018.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of chondral knee defects using a collagen membrane – autologus matrix-induced chondrogenesis

Abstract: ObjectivesTo evaluate the clinical and functional results of patients diagnosed with full-thickness chondral defects on symptomatic knees who underwent a biological repair technique using autologous matrix-induced chondrogenesis.MethodsSeven patients who underwent surgical treatment due to chondral lesions in the knee by autologous matrix-induced chondrogenesis were evaluated. The Lysholm, Kujala and visual analog scale of pain questionnaires were applied before and 12 months after the surgery. Nuclear magneti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 19 publications
0
4
1
3
Order By: Relevance
“…These results show agreement with the previous study published by our group. 24 There was no significant impact of age and BMI on the results found in the present study.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…These results show agreement with the previous study published by our group. 24 There was no significant impact of age and BMI on the results found in the present study.…”
Section: Discussioncontrasting
confidence: 52%
“…Esses resultados mostram concordância com o estudo anterior publicado pelo grupo. 24 Não houve impacto significante da idade e IMC nos resultados encontrados neste estudo.…”
Section: Discussionunclassified
“…6 Previous surgical techniques have demonstrated a variety of MRI-based cartilage repair characteristics. The present surgical technique has demonstrated higher MOCART scores compared to microfracture and collagen membrane matrix, 14 microfracture and a chitosan-based polymer scaffolding biomaterial, 15 mesenchymal stem cells, 16 and cell-free scaffold with collagen and hydroxiapatite. 17 Interestingly, Christensen et al reported the outcomes of a dual-tissue transplantation technique for osteochondritis dissecans in which autologous bone and cartilage tissue were used.…”
Section: Discussionmentioning
confidence: 79%
“…19,20 Cugat et al 2 reported a mean MOCART score of 70 (a score of 100 represents completely healthy cartilage) at 12 months using PACI technique , which was greater when compared with microfracture and collagen membrane matrix, microfracture, and chitosanbased polymer scaffolding biomaterial, mesenchymal stem cells, and cell-free scaffold with collagen and hydroxyapatite. [21][22][23] Massen et al 9 reported a mean MOCART score of 40.6 AE 21.1 at 6 months, and similar results were reported by Christensen et al 24 observed a MOCART score of 52.5 at 1 year after a particulate cartilage procedure, and Niemeyer et al 25 observed a long-term (follow-up of 10.9 years) MOCART score of 44.9 AE 23.6 after first-generation ACI.…”
Section: Discussionmentioning
confidence: 54%